On the veneration of ﬁre and good wishes in the Altai ritual system - A. I. Naeva (Nomadic Civilization: Historical Research)
The cult of ﬁre in the past and at the present time remains the most revered in the rituals of the Altaians. The author focuses on the rituals of worship of ﬁre in the calendar, family and household rites of the ethnos, traced in diﬀerent ritual situations. The Altai people in ancient and very recent times genuinely believed that at the moments of performing one or another vital rite, they, directly or through shamans, communicate with deities, spirits. The cult of ﬁre was also one of the central in the tradition of many Turkic-Mongolian peoples. Therefore, the author considers the ﬁre worship ceremony of the Altaians in comparison with similar rites of the genetically close peoples of the Turkic-Mongolian symbiosis (the Buryats, Kalmyks, Bashkirs, etc.). These peoples use the key magic words (blessings), which form an important part of ritual rites. They regulate the relationship between people within the framework of accepted social statuses and roles, occupying a signiﬁcant place in the spiritual culture of society.